Comparative Study of Cu and Fe-Doped ZnO Nanoparticles: Synthesis, Characterization, and Multifaceted Bioactivities - masome Naseri Tekyeh; Dariush Mehrparvar; Rostam Moradian; Shahriar Mahdavi; Maryam Rahimi; Mohammad Shahpouri (Progress in Physics of Applied Materials)
Metal oxide nanoparticles display significant roles in antimicrobial and anticancer activities. In the present study, Cu, and Fe-doped ZnO nanoparticles have been synthesized and investigated for their antioxidant, antibacterial, and anticancer properties. The above-mentioned nanoparticles have been synthesized by the low-cost and simple sol-gel method. The 2,2-Diphenyl-1-picrylhydrazyl (DPPH) assay was conducted to assess the antioxidant activity. The antibacterial activity of NPs was tested against E. coli and S. aureus bacteria according to the broth microdilution method in Mueller Hinton Broth. The anticancer potency on cancerous AsPC-1 cell lines was examined. The structural and morphology of samples confirm that all NPs formed with different crystallite sizes in the hexagonal wurtzite system. The DPPH assay showed the Zn1-XCuXO to have more antioxidant properties than other samples. We observed that the S. aureus bacterium is more sensitive to NPs than the E. coli bacterium. The strongest and weakest substances used for these bacteria are Zn1-XCuXO and Zn1-XFeXO NPs, respectively. Our anticancer results showed that the loaded drug on the NPs surfaces has more anticancer properties than pure drugs. ZnO and Zn1-XFeXO NPs possess similar anticancer properties approximately, while sunitinib@Zn1-XCuXO eliminates 92% of cancer cells at 200 μg/ml concentration. We observed that ZnO, Zn1-XFeXO, and Zn1-XCuXO NPs have antioxidant, antibacterial, and anticancer properties. Adding copper dopant to ZnO NP significantly increases its anticancer property.